2023
DOI: 10.1111/iwj.14209
|View full text |Cite
|
Sign up to set email alerts
|

Selective detection of urease‐producing bacteria on the genital skin surface in patients with incontinence‐associated dermatitis

Abstract: We aimed to investigate the association between the presence of cutaneous urease‐producing bacteria and the development of incontinence‐associated dermatitis (IAD) using an original urea agar medium as a step toward developing advanced preventive measures. In previous clinical assessments, we developed an original urea agar medium to detect urease‐producing bacteria via the medium's colour changes. In a cross‐sectional study, specimens were collected via the swabbing technique at genital skin sites in 52 strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“… 30 , 31 , 32 A 2023 study of incontinent adult patients with IAD by Kota et al showed a significant correlation between urease expressing bacterial on the skin of the patients and IAD incidence. 33 The most frequently associated pathogens in IAD infections include Candida albicans ( C. albicans ) from the gastrointestinal tract, and S. aureus , from the perineal skin 2 , 19 , 34 The elevated pH (from ammonia) also enhances the activity of faecal enzymes including proteases and lipases. 4 , 19 , 26 , 36 Ammonia is a caustic chemical which at sufficiently high concentrations, can cause chemical burns.…”
Section: Introductionmentioning
confidence: 99%
“… 30 , 31 , 32 A 2023 study of incontinent adult patients with IAD by Kota et al showed a significant correlation between urease expressing bacterial on the skin of the patients and IAD incidence. 33 The most frequently associated pathogens in IAD infections include Candida albicans ( C. albicans ) from the gastrointestinal tract, and S. aureus , from the perineal skin 2 , 19 , 34 The elevated pH (from ammonia) also enhances the activity of faecal enzymes including proteases and lipases. 4 , 19 , 26 , 36 Ammonia is a caustic chemical which at sufficiently high concentrations, can cause chemical burns.…”
Section: Introductionmentioning
confidence: 99%